The effect of intra-seasonal variation in precipitation on the productivity of grasses and grasslands - Swemmer, Anthony Michael, author; Knapp, Alan, advisor; Hartnett, David C., committee member; Hanan, Niall, committee member; Coughenour, Michael, committee member (Colorado State University. Libraries, 2007)
Above-ground net primary productivity (ANPP), a fundamental process in terrestrial ecosystems, varies greatly between years particularly in grasslands. While annual precipitation is considered the primary determinant of ANPP in grasslands, much of the inter-annual variation in ANPP cannot be explained by total annual or seasonal precipitation alone. It was hypothesized that intra-seasonal variation in precipitation can account for some of the unexplained variation in ANPP, and that two other factors known to affect grassland ANPP (community composition and grazing) can alter the relationship between ANPP and precipitation. To test the importance of intra-seasonal variation in precipitation, long-term ANPP data for three C4 grassland sites were analyzed. The effect of the average size, number and interval between rainfall events was determined and compared with that of annual precipitation. A field experiment was conducted at seven sites in undisturbed grasslands and savannas to investigate differences in growth responses to rainfall amongst co-occurring C4 grass species, and to determine the effect of defoliation on these responses. A pot experiment was conducted to determine eco-physiological mechanisms responsible for differences in tolerance of water stress between two species dominant in mesic grasslands. It was found that intra-seasonal variation in precipitation can explain as much of the inter-annual variation in ANPP as annual precipitation, but that the relative importance of each varies between sites. Changes in grass community composition within sites had a relatively small effect on the relative importance of each. A lack of synchrony of intra-seasonal growth amongst cooccurring C4 species was found in the field experiment. In the absence of grazing, intraseasonal variation in growth rates was primarily determined by water availability at different depths for co-occurring species. Regular defoliation increased synchrony amongst species, and resulted in more similar growth responses to soil water. A number of above-ground traits were identified which could predict aspects of soil water utilization and defoliation tolerance. These results indicate that intra-seasonal variation in precipitation can be an important determinant of grassland ANPP, and that any effect of changes in community composition on ANPP-precipitation relationships is likely to be reduced by heavy grazing.
Keywords: ecology; range management